Quality monitoring of the accounting profession : are we ready for peer review? / Normah Omar, Mohd Johari AIwi and Zaini Ahmad - Omar, Normah; AIwi, Mohd Johari; Ahmad, Zaini (Faculty of Accountancy, 2003)
One of the main concerns of the accounting profession is to provide consistently high quality services. In line with this objective, the current study was conducted for three main purposes: to determine the level of internal quality control and documentation amongst public accounting practices in Malaysia; to examine the role of the Malaysian Institute of Accountants (MIA) in ensuring members' compliance to the International Standards of Auditing (Al) on Internal quality and documentation, and to explore the potential of using peer review as a tool for monitoring the quality of public practices in Malaysia. The findings implied that the practitioners have satisfactorily adopted quality control policies and procedures as required by the International Auditing Standards. In addition, the public accounting firms were also found to have placed significant attention to the form and content of documentation as stipulated by the Als. The potential of using peer review as a quality-monitoring tool has strong support amongst the locally established public practices.